THE EFFECT OF SELF CONTROL AND FINANCIAL LITERATION FOR STUDENT’S SAVING BEHAVIOR - Evi Aulia Rachma (Jurnal Pendidikan Ekonomi, 2019)
Problems that occur in adolescents at this time in addition to the low awareness of saving also the high level of consumptive which tends to a wasteful lifestyle. This illustrates that teenager's self control is still lacking. Whereas in the current era of globalization, knowledge, skills, and understanding of finance are needed. Students must have sufficient financial literacy to manage their finances. Through these problems this study aims to determine the effect of self-control and financial literacy on saving behavior. This type of research is quantitative descriptive research. The research instrument used a questionnaire distributed to 250 students of SMAN 1 Sukodadi Lamongan. The instrument testing data technique used in this study included validity test and reliability test with Cronbach Alpha. Whereas to prove the research hypothesis with T and F Test. Analysis of the data used is multiple linear regression analysis. Based on the results of the study it can be concluded that self-control and financial literacy partially and simultaneously influence the saving behavior of SMAN 1 Sukodadi Lamongan students.